Matrix Analysis on Leading Term of Condition Number for Additive Schwarz Methods (Journal of Computational Mathematics, 2001)
It is well known the order of preconditional matrix by using additive Schwarz methods. In order to estimate the resulted PCG iteration counts, the related leading term before the order is given in this paper.
Keywords: Additive Schwarz method; PCG; Matrix analysis.